A habitually open mouth posture leads to less affect strength during joy in childhood - Wibke Bein-Wierzbinski; Sr. Maria Gabriela Franke; Christiane Heidbreder-Schenk (Discover Psychology, 2024)
Abstract Aim Compared with children without orofacial disorders, children with a habitual lack of mouth closure and mouth breathing show less frequent and reduced or absent facial expressions. The facial feedback hypothesis states that affective sensation is enhanced by mimic involvement. In this randomized cross-sectional study with and without orofacially disordered children, we investigated the effect of lack of mouth closure on the strength of emotions related to joy, sadness and fear in children. We aimed to determine whether kindergarten and primary school-age children with a lack of mouth closure are less emotionally involved. Materials and Method We used facial feedback as an indicator to measure affect intensity in children with and without orofacial disorders. For this purpose, we modified the experimental design of Strack et al. (Strack et al. in J Pers Soc Psychol 54:768–777, 1988), in which the subjects were asked to hold a pencil exclusively with their teeth (experimental group 1, “joy”), with their lips (experimental group 2, “sadness” and “fear”) or with their nondominant hand (control group). Instead of cartoons, ten medium-funny animal pictures were presented individually in a predefined order to be judged on a Likert scale. The allocation to the groups was implemented using a randomized procedure, independent of the diagnosis, age and sex of the children. The only exclusion criteria were the presence of surgical scars in the orofacial area and cerebral palsy. Results A total of 414 children aged 4 to 17 years were studied for facial feedback, with orofacial disorders such as open mouth posture, tongue thrust, myofunctional disorder, craniomandibular dysfunction (CMD) and speech motor disorders diagnosed in 223 subjects. The significance tests showed that in all age groups, children with orofacial disorders rated the joke content of the animal pictures significantly lower than did children without orofacial disorders (4- to 6-year-olds: p value = 0.01, T value = 2.33, confidence = 99%; 7- to 8-year-olds: p value = 0, T value = 4.98, 100% confidence; 9- to 17-year-olds: p value = 0, T value = 2.87, 100% confidence). This finding indicates that children with a lack of mouth closure and other orofacial disorders not only express less pleasure with the help of facial expressions but also feel less pleasure. Moreover, the experimental setup used in this work, which has been modified for children, can be used to test facial feedback in young subjects. Conclusion In our study, we focused on the interplay between physical and emotional development in children. If left untreated, children with a lack of oral closure may not only show deviations in the orofacial area later on, but also in their emotionality. We endeavored to highlight the importance of treating children with orofacial disorders at an early age.